Propagation, Selection And Establishment of Clonal Seed Orchard of Chilgoza Pine (Pinus gerardiana Wall.) - Singh, N. B. (Indian Forester, 1992)
Clonal propagation was standardized in Chilgoza pine. 20 plus trees were selected from 15 different places of Kinnaur in Himachal Pradesh. Information on variability, heritability and expected genetic gain (genetic advance as percent of mean) were obtained for eight cone and nut characters. In general, heritability estimates were quite high for most of the characters. Seed weight per cone provides lot of variability, high heritability and maximum genetic gain 29.47 followed by seed length and number of seeds per cone, Seed weight per cone should be given top priority for selecting the high yielding genotypes. Experimental clonal orchard was established by using three plus trees.